Krisis Ilmu Pengetahuan Modern: Menuju Metodologi Partisipatif - Hilwati Hindersah (Journal of Regional and City Planning, 2005)
Positivistic methodology has a very determining role in the development of modern science. To begin with, science is applied only to the physical universe. Science began to focus on this physical world and quickly flourished into a philosophical position that was quickly embraced as the reigning worldview for the modern age. This view further advocated an empirical skepticism in which nothing about the universe "“ seen as objects "“ should be believed unless it was shown by quantitative experiment to exist without question. Other human experiences of qualitative nature are outside the legitimate domain of scientific enquiry. Science became consumed with a purely secular and material focus. However, modern science has created crisis of unintended results. At the end of the twentieth century, we can see the grand results of this narrow focus on material progress, such as over exploitation of natural env ironment to the level of destruction and human alienation of technological progress. Subsequently an important turning point has emerged in the formation of the modern worldview. An alternative participative methodology has emerged to encounter this crisis. Participative methodology is defined as participative, educative and less controlled  research methodology that lead to a more holistic scientific knowledge.Keywords: science, research, participative methodology